Incidence and predictors of antiretroviral resistance in perinatally HIV-1 infected children and adolescents (2016)
Objectives Individuals with perinatally acquired HIV infection have benefited from antiretroviral therapy. However, they often have complex patterns of major resistance mutations that limit the effectiveness of available antiretroviral medications. Knowledge of incidence rates of major antiretroviral resistance mutations should provide a benchmark enabling comparisons of different HIV care delivery modalities. Methods We test the hypothesis that incidence rate of major antiretroviral resistance mutations will decline with improvement in HIV care between 1998 and 2009 to NRTI, NNRTI, PI and triple class resistance in perinatally HIV infected individuals. Logistic regression is used to evaluate predictors of single and triple class resistance. Results Sixty-six individuals are included from a total population of 97 perinatally HIV infected individuals. The incidence rate of NRTI, NNRTI, PI and triple class resistance decreases with decreasing age in parallel with the introduction of new HIV treatment regimens. The youngest children (born 2000–2007) are free of triple class resistance. Mono-therapy associates with major resistance mutations to NRTI (OR 8.7, CI 1.5–50.9, P 0.02); NNRTI exposure associates with major resistance mutations to NNRTI (OR 24.4, CI 5.7–104.5, P 0.01) and triple class resistance (OR 10.7, CI 1.8–67.1, P 0.01). Cumulative viral load is an important predictor of PI resistance (OR 4.0, CI 1.3–12.3, P 0.02). Conclusions There is a progressive decrease in the incidence rate of major resistance mutations to antiretroviral drugs and triple class resistance from the oldest to the youngest birth cohort; where adolescents have the highest risk of harboring resistant viruses. The incidence rate of major antiretroviral resistance mutations provides a benchmark for the comparative measurement of effectiveness of different HIV care delivery modalities.